L’interprétation online par les co-participants de la structuration du tour in fieri en TCUs: évidences multimodales - Mondada, Lorenza (My University, 2007)
This paper deals with a central notion of interactional linguistics, the "turn-constructional unit" (TCU), which organizes turns at talk as they are locally managed by the participants. Thus, the paper begins with a reminder concerning the place of TCU within the turn- taking model (Sacks, Schegloff & Jefferson, 1974) and within the literature in interactional linguistics. The latter works on the way in which linguistic resources are exploited in a situated and sequentially sensitive manner for the construction of turns. On this basis, the paper focuses on a central problem for the endogenous definition of TCUs: these units are flexibly, dynamically, actively achieved by the participants in the course of their actions; therefore the question is how can we demonstrate participants' actual orientations towards the emergence, organization and completion of TCUs? The paper answers to this question by looking at gestures as emboding the local interpretation of TCUs by the participants. In this way, the paper contributes to a better understanding of TCUs as units locally defined not only thanks linguistic resources but also thanks multimodal resources, for all practical purposes.